Study of photodetector for the application of autonomous vehicles - Sun, Yue (Nanyang Technological University, 2021)
Through a brief review of terahertz (THz) technology, this article briefly introduces the development and research status of terahertz technology, summarizes the special characteristics such as the low energy, high penetration, fingerprint spectrum, broadband, transient and coherence of terahertz waves, etc. Terahertz radar has strong technical advantages due to its high range resolution, large signal bandwidth, strong penetration, low interception rate, strong anti-jamming, superior anti-stealth and plasma penetration capabilities, has gained in the field of radar detection with a great application. At present, the field of autonomous driving is facing great environmental uncertainty, so the application of terahertz technology can be well implanted. Compared with traditional high-frequency signals, terahertz signals are more sensitive to the material and surface of the target because of the short wavelength. Terahertz LiDAR will be important equipment for target detection and recognition in the future. With the advancement of system integration technology, the entire LiDAR system can be designed to be smaller, so terahertz LiDAR can be used for high-resolution imaging radars for autonomous vehicles. The three mainstream sensors to realize unmanned driving of automobiles are optical cameras, LiDARs and millimeter wave radars. As optical sensors, optical cameras and LiDARs have the shortcomings of short coverage distance and poor weather work. The millimeter wave radar has a long detection distance and is not affected by bad weather work; but it cannot identify the shape of an object and has a low resolution, which is mainly used for obstacle avoidance. The terahertz wave, like millimeter waves, is not easily interfered by weather and light; compared to optical cameras and LiDARs, terahertz automotive radars will not greatly degrade in performance even in severe weather; and the functions are similar to LiDARs. In addition to the detailed review, an antenna-assisted metal-InGaAs-metal photodetector designed for 0.166 meV radiation is simulated and characterized, which is found to be useful for the application in the autonomous vehicle.